El camino a ser gente (sunna gua mhuysqa). La experiencia del fundamento telúrico y radical del saber ancestral indÍgena en Colombia (2023)
The weave presented here comes from recognizing in the mestizo root that spins our lineages as a race as American / Colombian people, the telluric and indigenous foundation that inhabits in us as a possibility of healing. Thus, the task of walking for years in the Colombian indigenous territory, its myths, traditions and rituals, has allowed the understanding of men sown spiritually on earth, in its pregnant womb, in the Hytcha Guaia. As a bridge to join a cosmogonic, mystical, epistemological, philosophical and psychic debate, the pretension is to return to the wisdom of our grandparents and grandmothers, to transcend the linear perspective, homogeneous and fractionated views of the academy, reality and health. A path of remembrance for the spiritual and original wisdom of fathers and mothers, who in their deepest, transforming and heartfelt senses bring men closer to becoming more humanistic. © 2018 Atlantis Press International. All rights reserved.